MANAJEMEN MUTU PENDIDIKAN OLEH KEPALA MADRASAH DI MTS IBNU TAIMIYAH SINGKAWANG - Agustina, Sri Endang; Aswandi, Aswandi; Wahyudi, Wahyudi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractÂ The purpose of this study is to obtain information and clarity of education quality management conducted by madrasah in MTs Ibn Taimiyah Singkawang.This study used descriptive qualitative. Sources of data in this study are the head of madrasah, teachers, education personnel, treasurer and chairman of the committee. Data collection was done in-depth interview technique, observation and documentation technique. Data analysis in this research is done by data collection, data areduksi, data presentation and conclusion. Check the validity of findings through extension of observation, increased perseverance in research, triangulation, discussion with peers and member checks.The results of the study concluded that (1) the planning of quality education program conducted by the head of madrasah has been running well, in accordance with the existing rules and regulations. (2) implementation of quality education work plan conducted by head of madrasah has been done well although not yet optimal. (3) supervision / evaluation of education quality by the head of madrasah is in accordance with the rules that have been established and through procedures in accordance with applicable provisions although not optimal in the implementation. (4) As for obstacles and challenges faced by the lack of complete facilities and infrastructure in supporting the learning in madrasah, human resources that are less professional and not fully qualified undergraduate and educational background that is not in accordance with the subjects that are diampu, lack of availability of complete library and the lack of empowered committees in madrasah because they have not been formed optimally.Â Keywords: Management, Quality of Education, Head of Madrasah.